Kreatifitas Guru dalam Proses Pembelajaran SBdP di Kelas V SDN 85/VII Semaran - Siswanto, Argi Eko; Habbah, Eka Sumbulatim Miatu; Kurnia, Fetiami Dwi; Ilham, Muhammad; Parastu, Rekhano Andria; Arista, Reni (ARZUSIN, 2022)
In the world of education, the teacher is a key success factor in achieving educational goals and improving the quality of learning. When studying SBdP in elementary schools, students still think that learning is difficult to understand, so teachers must have high creativity to teach this. Creativity in this case is a person's ability to create new products, both in the form of ideas and in real works, which are relatively different from those that existed before. The type of research method used is qualitative research, namely research used to describe and analyze phenomena, events, social activities, beliefs, perceptions, and people individually and in groups (Sukmadinata, 2009:53-60). The research objective is teacher creativity in the SBdP learning process in class V at SD Negeri No. 85/VII Semaran. The location used as the research site is SD Negeri No. 85/VII Semaran, Pauh District, Sarolangun Regency, Jambi. Creative educators are expected to be able to help realize the creativity of students. Therefore, an educator must be able to determine the right learning approach and determine the success criteria of a lesson. Each student has a different character, even has unique strengths, weaknesses, interests and talents, and attention that is not the same as that of other students. Based on the description of the explanation that has been explained above, creativity is something that must exist in a person in order to realize something that can produce something both in educational life and for everyday life.